UNICASH: POINTS CHECKOUT (CIPEEX, 2022)
UNICASH IS A MOBILE APPLICATION FOR €‹€‹SCORING STUDENTS ASSIGNMENTS AVAILABLE FROM WITHIN THE UNIVERSITY€™S VIRTUAL LEARNING MANAGEMENT SYSTEM (MOODLE), AND RETURNING SCORES AS A BALANCE FOR THE STUDENTS TO SPENT ON COMMERCIAL ESTABLISHMENTS AT THE UNIVERSITY€™S CAMPUS. ITS FEATURES INCLUDE POINTS EXCHANGE FROM WITHIN A CATALOG OF GOODS AND SERVICES, POINTS CHECKOUT, EXCHANGING POINTS BETWEEN STUDENTS, SCORES RANKING, AND REPORTS. THE GROUP AUTHORING THIS DOCUMENT IS RESPONSIBLE FOR THE POINTS CHECKOUT FEATURE IN WHICH COMMERCIAL REPRESENTATIVES DEBIT STUDENT'S POINTS AFTER PROPER CONFIRMATION. THE APPLICATION DISPLAYS THE STUDENT€™S ORDERS IN A LISTING FOR THE REPRESENTATIVE; WHEN THE REPRESENTATIVE OPENS AN ORDER, THE APP DISPLAYS THE ITEMS WHICH THE STUDENT HAS SELECTED. THEN, THE REPRESENTATIVE WILL HAVE A MAXIMUM OF FIVE MINUTES TO COMPLETE THE ORDER, OTHERWISE UNICASH DISCARDS IT. TO COMPLETE THE ORDER, THE REPRESENTATIVE NEEDS TO INPUT THE CODE FROM THE STUDENT€™S APPLICATION SCREEN, AND THEN UNICASH EXCHANGES THE POINTS. IN THE PROJECT€™S INITIATION PHASE, ALL GROUPS CONTRIBUTED SKETCHES IDEALIZING THE APPLICATIONS€™ INTERFACE, AND THEN ITERATED TO A STANDARDIZED DESIGN. THE GROUP AUTHORING THIS DOCUMENT WENT THROUGH DEVELOPMENT PHASES INCLUDING PROTOTYPING SCREENS WITH FIGMA BASED ON THE STANDARDIZED DESIGN FOR THE POINT CHECKOUT FEATURE. FOR TASK MANAGEMENT, THE GROUP USED TRELLO, WITH A TASK BOARD FOR EACH TEAM CONTAINING THEIR RESPECTIVE ATTRIBUTIONS, STATES AND CUSTOM WAYS OF DOCUMENTING. FOR THE CONSTRUCTION PHASE, THE GROUP CHOSE POSTGRESQL FOR THE DATABASE, PYTHON AND FLASK FOR THE BACKEND, AND REACT NATIVE FOR THE FRONTEND. FOR DEVELOPMENT OPERATIONS, THE GROUP USED CONTAINER VIRTUALIZATION (DOCKER/PODMAN) IMPLEMENTING A CONTAINER IMAGE FOR THE BACKEND, AND CONTAINER COMPOSE WITH SERVICES FOR THE BACKEND AND DATABASE, AND NETWORK CONNECTION BETWEEN THEM. THIS PROJECT IS PART OF THE MOBILE APPLICATION DEVELOPMENT COURSE FOR THE FIFTH AND SIXTH PERIODS OF THE SOFTWARE ENGINEERING PROGRAM AT THE UNIVERSIDADE EVANGÉLICA DE GOIS, 2022/2 SEMESTER.
Keywords: mobile; application; android